Scrutinizing transport phenomena and recombination mechanisms in thin film Sb2S3 solar cells - Z. Younsi; F. Meddour; H. Bencherif; M. Khalid Hossain; Latha Marasamy; P. Sasikumar; M. S. Revathy; Suresh Ghotekar; Mohammad R. Karim; Manikandan Ayyar; Rajesh Haldhar; Mirza H. K. Rubel (Scientific Reports, 2024)
Abstract The Schockley–Quisser (SQ) limit of 28.64% is distant from the Sb2S3 solar cells’ record power conversion efficiency (PCE), which is 8.00%. Such poor efficiency is mostly owing to substantial interface-induced recombination losses caused by defects at the interfaces and misaligned energy levels. The endeavor of this study is to investigate an efficient Sb2S3 solar cell structure via accurate analytical modeling. The proposed model considers different recombination mechanisms such as non-radiative recombination, Sb2S3/CdS interface recombination, Auger, SRH, tunneling-enhanced recombination, and their combined impact on solar cell performance. This model is verified against experimental work (Glass/ITO/CdS/Sb2S3/Au) where a good coincidence is achieved. Several parameters effects such as thickness, doping, electronic affinity, and bandgap are scrutinized. The effect of both bulk traps located in CdS and Sb2S3 on the electrical outputs of the solar cell is analyzed thoroughly. Besides, a deep insight into the effect of interfacial traps on solar cell figures of merits is gained through shedding light into their relation with carriers’ minority lifetime, diffusion length, and surface recombination velocity. Our research findings illuminate that the primary contributors to Sb2S3 degradation are interfacial traps and series resistance. Furthermore, achieving optimal band alignment by fine-tuning the electron affinity of CdS to create a Spike-like conformation is crucial for enhancing the immunity of the device versus the interfacial traps. In our study, the optimized solar cell configuration (Glass/ITO/CdS/Sb2S3/Au) demonstrates remarkable performance, including a high short-circuit current (J SC ) of 47.9 mA/cm2, an open-circuit voltage (V OC ) of 1.16 V, a fill factor (FF) of 54%, and a notable improvement in conversion efficiency by approximately 30% compared to conventional solar cells. Beyond its superior performance, the optimized Sb2S3 solar cell also exhibits enhanced reliability in mitigating interfacial traps at the CdS/Sb2S3 junction. This improved reliability can be attributed to our precise control of band alignment and the fine-tuning of influencing parameters.